PENGARUH EARNING PER SHARE (EPS) TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA (BEI) TAHUN 2016-2020 - Yunika, Devita Tri; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
Investment is a commitment to invest a number of funds or other resources that are carried out at this time with the aim of obtaining a number of benefits in the future. Development in the capital market shows that progress in line with the increase in the Index shown in the LQ45 Index. LQ45 Index based the company with high liquidity and a large market capitalization which consists of 45 companies. The purpose of this study was to analyze and examine the influence of Earning Per Share (EPS) on stock returns with dividend policy as an intervening variable. This research uses descriptive and quantitative research methods. The population in this research are companies listed in the LQ45 Index with a sample of 7 companies. The sampling technique used was purposive sampling technique. Data analysis and hypothesis testing in this study used the Stuctural Equation Model – Partil Least Square (PLS-SEM). The results of the analysis using the smart partial least square (PLS) 3.0 software, show Earning Per Share (EPS) has a significant negative effect on Dividen policy, Earning Per Share (EPS) has a significant positive effect on Stock returns, Dividend policy is not proven to have a significant effect on stock return. The results of influential hypothesis that are not immediately pointed to the Earning Per Share (EPS) variable against Stock return with Dividend policy as a variable of intervening has a positive but insignificant effect.